(untitled) (Revista de Investigaciones Universidad del Quindío, 2012)
Studies in the Quindío and Colombia have reported that HDL is below that levels recognized as normal, howe-ver, the situation is unknown about the apoA-I, MMP2 and MMP9; important variables in the cardiovascular risk (CVR) recognition, especially in young people. Objective: to determine the lipid profile, HDL2 and HDL3 subpopulations, apoA-I, MMP2 and MMP9 serum levels, and establish a relationship between these variables. Methods: The study was conducted at students aged 18 to 29 years. The HDL2 and HDL3 subpopulations were measured by ion precipitation method, the ApoA-I, MMP2 and MMP9 were measured by ELISA. Results: Lipid profile was normal, except for low HDL, despite having normal apoA-I. HDL2 and HDL3 subpo-pulations were found in similar levels (17.31 ± 5.90 and 17.99 ± 6.70 md/dl), respectively, without significant differences between them. MMP2 and MMP9 were 51.05 ± 5.69 ng/ml and 5.29 ± 3.03 ng/ml respectively. Structural analysis found a complex interaction between anthropometric, physiological and biochemical va-riables as: apoA-I, HDL2 and HDL3 subpopulations; between SBP and DBP; between MMP2 and MMP9. Between BMI and apoA-I; corporal weight with HDL2, HDL3, SBP, DBP and MMP2. And between waist circumference with apoA-I, SBP, DBP, MMP2 and MMP9. Conclusions: This study reveals a normal biochemical and physiological state, with interactions between varia-bles, which is compatible with healthy young organisms homeostasis, except fo rthe low total HDL.